2019
DOI: 10.3390/pathogens9010005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Pathogenicity, Virulence, Antibiotic Resistance, and Phylogenetic Analysis of Biofilm-Producing Listeria monocytogenes Isolated from Different Ecological Niches in Egypt: Food, Humans, Animals, and Environment

Abstract: Serious outbreaks of foodborne disease have been caused by Listeria monocytogenes found in retail delicatessens and the severity of disease is significant, with high hospitalization and mortality rates. Little is understood about the formidable public health threat of L. monocytogenes in all four niches, humans, animals, food, and environment, in Egypt. This study analyzed the presence of L. monocytogenes collected from the four environmental niches and bioinformatics analysis was implemented to analyze and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 92 publications
(139 reference statements)
2
22
4
1
Order By: Relevance
“…The prevalence of L. monocytogenes in the present study was slightly higher than the reports of 8.0% by Weber et al [ 28 ], 4.36% by Kalender [ 15 ], 8.0% by Abd El-Malek et al [ 16 ], 7.14% by Al-Ashmawy et al [ 29 ], 4.0% by Awadallah and Suelam [ 30 ], 4.2% by Shaker and Hassanien [ 31 ], and 7.5% by Osman et al [ 32 ]. On the contrary, Rahmat et al [ 33 ] detected the bacterial pathogen in 62.5% of poultry meat samples, and Carvalho et al [ 34 ] detected L .…”
Section: Discussioncontrasting
confidence: 74%
“…The prevalence of L. monocytogenes in the present study was slightly higher than the reports of 8.0% by Weber et al [ 28 ], 4.36% by Kalender [ 15 ], 8.0% by Abd El-Malek et al [ 16 ], 7.14% by Al-Ashmawy et al [ 29 ], 4.0% by Awadallah and Suelam [ 30 ], 4.2% by Shaker and Hassanien [ 31 ], and 7.5% by Osman et al [ 32 ]. On the contrary, Rahmat et al [ 33 ] detected the bacterial pathogen in 62.5% of poultry meat samples, and Carvalho et al [ 34 ] detected L .…”
Section: Discussioncontrasting
confidence: 74%
“…The main virulence factors like prfA, hly, plcA, inlA, inlB involved in the pathogenesis of L. monocytogenes were observed in all the analyzed isolates. PrfA is a major transcriptional activator of L. monocytogenes virulence genes [47,48]. When L. monocytogenes enters a host cell, it is primarily located in single-membrane vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…Montero et al [ 25 ] and Vilchis-Rangel et al [ 38 ] reported similar percentages (20–40%) for LIPI-1 in L. monocytogenes isolates from orange juice, vegetables, and frozen vegetables. Moreover, several studies have reported LIPI-1 in 100% of L. monocytogenes isolates from duck, beef, pork, chicken, vegetables, fried rice, fish, goat meat, pasteurized milk, and yogurt [ 13 , 39 , 40 ]. The wide range of virulence-associated L. monocytogenes genes found in this study could be associated with food type, sources, mechanisms of contamination during food processing and marketing, epidemiological factors, countries, geographical differences, the genetic diversity of strains, and methodologies for the serotyping of L. monocytogenes in food.…”
Section: Discussionmentioning
confidence: 99%